INSTALASI MIKROTIK PADA VIRTUALBOX DAN CONFIGURASI SETTING HOTSPOT DAN PPPOE DENGAN WINBOX DI UKM ROBOTIK - Dikri Wahyu Ilahi; Abdus Samad (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study explores the implementation of the MikroTik RouterOS network operating system in a virtual environment using VirtualBox, as well as the configuration of two key network services—Hotspot and PPPoE—through the graphical interface tool Winbox. Virtualization was chosen as the primary method to eliminate the need for physical hardware and to provide flexibility in network simulation. After successfully installing RouterOS, basic network settings were applied prior to setting up Hotspot and PPPoE services. Winbox was used to streamline administrative tasks and monitoring processes. Test results showed that both services functioned properly, supported user authentication, and delivered stable connectivity. This approach proved to be effective for training, testing, and small to medium-scale network development.